Plasma Drug Concentration of Propranolol and Genetic Study in Chinese Han Patients With Infantile Haemangioma - Li, Li; Yu, Lu; He, Huan; Wei, Li; Xu, Zigang; Zhao, Libo; Sun, Yujuan; Zhang, Bin; Liu, Yuanxiang; He, Rui; Wang, Xiaoling; Ma, Lin (Frontiers in Pediatrics, 2022)
Background and Purpose: To explore plasma drug concentration of propranolol in Chinese Han patients with infantile hemangioma and influenced factors, and the relationship among plasma drug concentration of propranolol, β1-AR mutation and CYP2D6 188C>T, efficacy and safety. Experimental approach: From January 2018 to April 2019, 140 patients with infantile hemangioma who were admitted to the hospital for oral propranolol and agreed to have their plasma concentration of propranolol, β1-AR mutation and CYP2D6 188C>T were tested, including 112 patients with β1-AR and CYP2D6 gene tested. Key Results and Conclusions & Implications: The mean peak blood levels of propranolol, 4-OH-P and NDP were 60.35±37.90, 1.90±2.37 and 0.24±0.18 ng/ml, respectively. The mean trough blood levels of propranolol, 4-OH-P and NDP were 24.98±17.68, 0.45±0.52 and 0.05±0.05 ng/ml, respectively. The higher the plasma concentration of propranolol, the better the treatment efficacy after 1 month (p=0.036). The plasma concentration of propranolol was positive related to the treatment efficacy after 1 month.